Pengembangan Media Pembelajaran Interaktif Berbasis Visual Basic for Application pada PowerPoint Menggunakan Pendekatan ADDIE - Moh. Alfa Rezi Ali; Sumarno Ismail; Yamin Ismail (Research in the Mathematical and Natural Sciences, 2026)
The use of instructional media in mathematics learning is often still static, resulting in low student engagement and increased boredom during the learning process. Therefore, interactive learning media are needed to enhance students’ interest and participation. This study aims to develop a mathematics learning media based on Visual Basic for Application (VBA) in Microsoft PowerPoint on the topic of sequences and series, and to evaluate its validity and practicality. This research employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research instruments included media validation sheets, material validation sheets, and questionnaires for teacher and student responses. The data were analyzed using the average percentage of assessment scores. The results showed that the developed learning media achieved a very high level of validity, with 92% from media experts and 91% from material experts. In addition, the practicality level was categorized as very practical, with 98% from teacher responses and 87% from student responses. Thus, the VBA-based PowerPoint learning media is considered valid and practical for use in mathematics learning, particularly on the topic of sequences and series.